2016
DOI: 10.1021/acs.jced.5b00803
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibria for Ternary Systems of Water + Methoxycyclopentane + Alcohol (Methanol, Ethanol, 1-Propanol, or 2-Propanol)

Abstract: Liquid–liquid equilibria data were determined for four ternary systems of water + alcohol + methoxycyclopentane (CPME); the alcohols used were methanol, ethanol, 1-propanol, and 2-propanol. All measurements were performed at 298.15 K and atmospheric pressure. Binodal curves were experimentally determined using both the cloud-point method and tie lines. The reliability of the tie-line data were verified by the Hand and Othmer–Tobias plots. Distribution coefficients and separation factors were determined from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
4
11
0
Order By: Relevance
“…Phase compositions are also shown in the tertiary diagrams ( Figure 5) and confirm that methanol ( Figure 5A) provides the best phase separation shown by the downward sloping line connecting point C (aqueous phase composition) and point D (organic phase composition). These results are in good agreement with Wales et al 18 who showed that the capability of CPME to extract alcohol from the aqueous phase was lowest in methanol followed by ethanol and 1-propanol.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Phase compositions are also shown in the tertiary diagrams ( Figure 5) and confirm that methanol ( Figure 5A) provides the best phase separation shown by the downward sloping line connecting point C (aqueous phase composition) and point D (organic phase composition). These results are in good agreement with Wales et al 18 who showed that the capability of CPME to extract alcohol from the aqueous phase was lowest in methanol followed by ethanol and 1-propanol.…”
Section: Resultssupporting
confidence: 92%
“…Results from testing biphasic systems of CPME:water:alcohol (ethanol/methanol/1-propanol) showed that methanol had the best oil extraction performance since it partitioned more readily into the aqueous phase. These results are in good agreement with ternary diagrams of CPME:water:alcohol (ethanol/methanol/1-propanol) developed by Wales et al 18 The researchers showed that phase separation of CPME from the aqueous alcohol portion was best using methanol as indicated by the lower capability (selectivity) of CPME to extract methanol from the aqueous phase. When extracted oil from wet yeast cells, all the systems of CPME:methanol:water had comparable TAG selectivity but the TAG extraction efficiency decreased as the ratio of CPME increased in the final phase.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It has also been studied in many important chemical processes including furfural synthesis [67] and extraction of natural products [68]. Previous works studied the liquid–liquid equilibria for ternary systems of water/CPME/alcohol (methanol, ethanol, 1-propanol, or 2-propanol) to test greener solvent systems that substitute and simulate the Bligh and Dyer method for oil extraction [69]. Recently, a comparative study of lipid extraction from wet microalgae was performed using several methods such as the Soxhlet, Bligh and Dyer, Folch, and Hara and Radin methods, with 2-methyltetrahydrofuran (2-MeTHF) and CPME as green solvents.…”
Section: Introductionmentioning
confidence: 99%